Engineering the Human Thymic Microenvironment to Support Thymopoiesis In Vivo. (18th August 2014) - Chung, Brile; Montel-Hagen, Amélie; Ge, Shundi; Blumberg, Garrett; Kim, Kenneth; Klein, Sam; Zhu, Yuhua; Parekh, Chintan; Balamurugan, Arumugam; Yang, Otto O.; Crooks, Gay M.
Abstract : A system that allows manipulation of the human thymic microenvironment is needed both to elucidate the extrinsic mechanisms that control human thymopoiesis and to develop potential cell therapies for thymic insufficiency. In this report, we developed an implantable thymic microenvironment composed of two human thymic stroma populations critical for thymopoiesis; thymic epithelial cells (TECs) and thymic mesenchyme (TM). TECs and TM from postnatal human thymi were cultured in specific conditions, allowing cell expansion and manipulation of gene expression, before reaggregation into a functional thymic unit. Human CD34+ hematopoietic stem and progenitor cells (HSPC) differentiated into T cells in the aggregates in vitro and in vivo following inguinal implantation of aggregates in immune deficient mice. Cord blood HSPC previously engrafted into murine bone marrow (BM), migrated to implants, and differentiated into human T cells with a broad T cell receptor repertoire. Furthermore, lentiviral-mediated expression of vascular endothelial growth factor in TM enhanced implant size and function and significantly increased thymocyte production. These results demonstrate an in vivo system for the generation of T cells from human HSPC and represent the first model to allow manipulation of gene expression and cell composition in the microenvironment of the human thymus. Stem Cells   2014;32:2386–2396